EVALUASI WAKTU PROSES SUPPLY SMALL PART DENGAN MEMPERHATIKAN BEBAN KERJA DI PT. TOYOTA MOTOR MANUFACTURING INDONESIA - Dene Herwanto; Rianita Puspa Sari (Jurnal Teknologi, 2018)
Section Internal Logistic PT. TMMIN has the task of supplying small parts from various suppliers to each post lane assembly. Time process used today is known as Gentan-i. Gentan-i has a shortage that tolerance time for man power is not calculated objectively, but overall between each process, so the workload of supply small part process route A is seemed so heavy and operator to work in hurry.This study aimed to evaluate the processing time of supply small part by taking into account the workload, so as to obtain better standard time for the operator. The study was conducted by means of direct observation of the working process of small parts supply by operator then retrieved the data processing time by stopwatch.The calculations show that the operator workload with Gentan-i time is higher than the workload with the standard time that takes into account the performance rating and allowance. One of the improvements to be proposed is to balance some tasks of route A supply to the other route so that the overall workload becomes more balanced.